Analisis Nilai Tambah Pengolahan Susu Sapi Dalam Upaya Meningkatkan Pendapatan Koperasi (Coopetition : Jurnal Ilmiah Manajemen, 2024)
Koperasi Peternakan Bandung Selatan (KPBS) Pangalengan has a business unit, namely PT.SKP which is a cow's milk processing industry to provide added value to milk to generate income and provide economic benefits to members. This study aims to find out: (1) how much added value of milk processing, (2) the income and cost efficiency of the cow's milk processing business, and (3) how far the added value from the processing of cow's milk in the PT. SKP business units can increase income and provide economic benefits for the members. The method is case study uses descriptive and analytic analysis, with purposive sampling. Data collected by interviews, observation and documentation. Data analysis uses added value analysis using the Hayami method and analysis of income and cost efficiency. The results are: (1). The added value of processing cow's milk into pasteurized milk was IDR 4,800 per liter or 31.37%, for yogurt it was IDR 8,500 per liter or 37.78%, while mozzarella cheese was IDR 1,200 per liter or 15%; (2) Income from processing cow's milk, in one production for pasteurized milk products is IDR 18,913,646 with an R/C ratio of 1.6, for yogurt products IDR. 9,719,346 with an R/C ratio of 1.9 while for mozzarella cheese products Rp.4,288,346 a ratio of 1.1; (3) The added value in the processing of cow's milk, the cooperative can increase its income from the provision of income from the PT.SKP business unit given to KPBS in the form of cooperation so that KPBS can provide economic benefits for members consisting of Direct Economic Benefits and Indirect Economy Benefit for cooperative members.